Vanilla Export Destination Country Selection Strategy in an Effort to Optimize the International Market : (Case Study of Cv. Tanda Sentra Indonesia) - Attaya Irhab Narendra; Didi Widia (Jurnal Impresi Indonesia, 2024)
Indonesia is the second largest producer of vanilla in the world. This is because Indonesia produces quality and durable vanilla. The subject of the case study and the main object of this research is CV Tanda Sentra Indonesia, which is a company that produces dried vanilla and works with local farmers under the guidance of the company. CV Tanda Sentra Indonesia has exported to several countries, namely Italy, France and the UK. However, the company still has obstacles in determining export destination countries to be able to cover other countries. Therefore, this study aims to (1) analyze vanilla export destination countries using the PESTEL method, (2) conduct a SWOT analysis of related export destination countries, and (3) identify export strategies in optimizing the vanilla market. The research method used in this study is a qualitative method using PESTEL analysis. For data collection techniques, descriptive methods were used and analyzed using the PESTEL and SWOT methods. Then, weighting was carried out using the SWOT matrix and IFAS and EFAS weighting.